2016
DOI: 10.1007/s40264-016-0398-9
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Prochlorperazine in Children: A Systematic Review and Meta-Analysis

Abstract: The most common AEs reported with the pediatric use of prochlorperazine are EPS and sedation. Fatalities, life-threatening, and persistent AEs have also been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The guideline recommendations are summarized in Table and Supplementary Table SVII. Studies evaluating ABH gel, 5‐HT3 antagonists, and prochlorperazine were included in the evidence summary but were omitted from the recommendations due to poor systemic bioavailability, inclusion as standard acute CINV prophylaxis[11] and safety concerns, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The guideline recommendations are summarized in Table and Supplementary Table SVII. Studies evaluating ABH gel, 5‐HT3 antagonists, and prochlorperazine were included in the evidence summary but were omitted from the recommendations due to poor systemic bioavailability, inclusion as standard acute CINV prophylaxis[11] and safety concerns, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore systematic reviews evaluating the safety of metoclopramide [5] and prochlorperazine [6] were undertaken, and an existing systematic review of the safety of olanzapine [7] in children was considered by the panel. Primary studies reported separately for patients ࣘ18 years of age or the mean or median age pf participants was ࣘ18 years; iii.…”
Section: Evidence Identification and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“… 26 Phenothiazines and butyrophenones have also been used in CINV, but their use, particularly when administered at a high dose, is limited by the risk of major extrapyramidal reactions (dystonia, parkinsonism and oculogyric crisis). 27 , 28 …”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…26 Phenothiazines and butyrophenones have also been used in CINV, but their use, particularly when administered at a high dose, is limited by the risk of major extrapyramidal reactions (dystonia, parkinsonism and oculogyric crisis). 27,28 Antagonists of 5-hydroxytryptamine3 (5-HT3) receptors (ondansetron, granisetron, tropisetron, palonosetron) are used in CINV control. 29 Palonosetron is a second-generation 5-HT3 receptor antagonist that has been shown to achieve better control of emesis compared with ondansetron, in children receiving highly or moderately emetogenic chemotherapy over several days.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%